The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/w9010028
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Groundwater Declines with Precision Agriculture: An Economic Comparison of Monitoring Methods for Variable-Rate Irrigation

Abstract: Irrigated row-crop agriculture is contributing to declining groundwater in areas such as the Mississippi Delta region of eastern Arkansas. There is a need to move toward sustainable levels of groundwater withdrawal. Recent improvements in remote monitoring technologies such as wireless soil moisture sensors and unmanned aerial vehicles offer the potential for farmers to effectively practice site-specific variable-rate irrigation management for the purpose of applying water more efficiently, reducing pumping co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
(41 reference statements)
0
12
0
1
Order By: Relevance
“…Such information can aid in improving irrigation efficiency, reducing pumping costs, and retaining groundwater. Although soil moisture sensors are found to be more profitable in the present context, with the increasing number of manufacturers and clear regulations, UAS-based sensor technology for soil moisture estimation is gaining momentum [114]. This explains the importance of remote sensing as a low-cost tool to improve water management in crops.…”
Section: Remote and Proximal Sensingmentioning
confidence: 99%
“…Such information can aid in improving irrigation efficiency, reducing pumping costs, and retaining groundwater. Although soil moisture sensors are found to be more profitable in the present context, with the increasing number of manufacturers and clear regulations, UAS-based sensor technology for soil moisture estimation is gaining momentum [114]. This explains the importance of remote sensing as a low-cost tool to improve water management in crops.…”
Section: Remote and Proximal Sensingmentioning
confidence: 99%
“…Precision irrigation and precision nitrogen fertilization are widely seen as an excellent method to save water and fertilizer and maximize yield (Zhao et al, 2017). On the other hand, several authors (Adeyemi, Grove, Peets and Norton, 2017;West and Kovacs, 2017) showed that the use of these technologies alone are not sufficient to increase the efficiency of the entire production process.…”
Section: Economic Studiesmentioning
confidence: 99%
“…In summary, the techniques in question also contribute to increased labour productivity. The benefits [60] resulting from using of PA technologies are derived from many key drivers (Vogt, 2017;Calegari et al, 2013;West and Kovacs, 2017): capital and annual operating costs associated with acquiringthe technology, impact of the technology on labour demand, impact on yield, product quality, cost savings, environmental benefits etc. Nevertheless Robertson et al (2008) argue, that the profitability of PA and benefits from PA technologies varies from farm to farm, in line with farmer preferences and circumstances.…”
Section: Introductionmentioning
confidence: 99%